(b) \( \frac{3}{p}+\frac{5}{2 p}-\frac{2}{p^{2}} \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Extra Insights
To simplify the expression \( \frac{3}{p}+\frac{5}{2 p}-\frac{2}{p^{2}} \), we first find a common denominator. The common denominator for all terms is \( 2p^2 \). Rewriting each term: - \( \frac{3}{p} = \frac{3 \cdot 2p}{2p^2} = \frac{6p}{2p^2} \) - \( \frac{5}{2p} = \frac{5 \cdot p}{2p^2} = \frac{5p}{2p^2} \) - \( \frac{2}{p^2} = \frac{2 \cdot 2}{2p^2} = \frac{4}{2p^2} \) Now, combine them: \[ \frac{6p + 5p - 4}{2p^2} = \frac{11p - 4}{2p^2} \] So, the simplified expression is \( \frac{11p - 4}{2p^2} \).